Les notions de fūkei, de ba et de fukkō au cœur d’un projet collectif artistique - Catherine Grout (Projets de Paysage)
This essay shows how a specific understanding of landscape (fūkei) as an agricultural landscape associated with the collective imagination, memory, and the activities related to vegetable farming enabled artist Taho Ritsuko to engage survivors of the Great Hanshin-Awaji Earthquake, which struck Osaka-Kōbe in 1995, in a movement of reconstruction and renewal (fukkō). The project involved the survivors in the entire process, from conception to realization, of a work intended for a communal outdoor space in the danchi (a new public housing complex) where they were being relocated. The project gained renown in Japan for the political and administrative battle won, which gave the survivors the right to independently cultivate part of the public land in the Minami-Ashiyahama district. By involving them in a creative process that became political, the artist aimed to encourage their interaction and create an active co-presence consistent with the notion of ba (scene, place, or field). Composed of two landscape sculptures, the work was integral to the process of forming and establishing a community.